Design of security verification platform for the integrated space-ground network - Zhi-chao QIN; Ping ZHANG; Xin-xin FAN; Zhou LU (网络与信息安全学报, 2016)
The integrated space and terrestrial network is complex,having diversified technical specifications which involves all aspects of the system of security technology,so it is difficult to achieve system level verification and evaluation through individual technology test.It is necessary to construct a certain scale of network authentication system to verify the effectiveness of safety technology architecture.Based on the concept of general opening and reconstruction,a scheme of integrated network security verification system was presented to validate security tech-nologies such as key management,secure routing,secure handoff,security isolation and secure transmission.